ANALISIS PENGARUH NPL, CAR, BOPO DAN IRR TERHADAP PERTUMBUHAN KINERJA KEUANGAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Nurul Ichsan, Reza; Nasution, Lukman (MONETER, 2020)
This study aims to determine whether NPL, CAR, BOPO, and IRR affect the growth of financial performance of banks listed on the IDX, either partially or simultaneously. This research method is multiple linear regression. The banking company studied was a foreign exchange National Private Commercial Bank (BUSN) listed on the Indonesia Stock Exchange (BEI). This study uses secondary data obtained from the Indonesia Stock Exchange website, namely www.idx.co.id using a sample of 16 companies from a population of 23 banking companies during the 2011-2015 period. From the research results obtained multiple linear regression equation Y = 0.995 + 0.002NPL– 0.008BOPO- 0.025CAR + 0.009IRR. The results of this study indicate that partially the IRR variable has an effect on ROA, while the NPL, CAR and BOPO variables have no effect on ROA while simultaneously NPL, CAR, BOPO, and IRR have an effect on ROA. The value of R = 0.716, meaning that the relationship between the variables NPL, OEOI, CAR and IRR on ROA is 71.6% or in other words the relationship between variables is strong. Meanwhile, the value of Adjusted R ^ 2 is 0.487 or 48.7%, which means that the effect of NPL, CAR, BOPO and IRR on Return on Assets (ROA) is 48.7%. While the remaining 51.3% is influenced by other variables which are not used in this study.